Is skin in the game a game changer? Evidence from mandatory changes of D&O insurance policies - Lin, Chen; Officer, Micah S.; Schmid, Thomas; Zou, Hong (Journal of Accounting and Economics, 2019)
This paper examines the incentive effects of a mandatory personal deductible in liability insurance contracts for directors and officers (D&Os). Exploiting a novel German law that mandates personal deductibles for executives, we document positive returns for affected firms around the first announcement of the plan to impose a personal deductible. We also find evidence of long-run effects: affected firms decrease risk taking in operational activities and financial reporting, and improve the quality of takeover decisions. Our study shows that the structure of D&O insurance contracts matters because mandating that D&Os have “skin in the game” appears to lead to real effects on firm value.